2016
DOI: 10.1007/s11998-016-9848-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding TiO2 nanoparticles to a water-based varnish for wood applied to nine tropical woods of Costa Rica exposed to natural and accelerated weathering

Abstract: The addition of titanium dioxide nanoparticles (TiO 2 nanoparticles) to a water-based varnish used for finishing tropical woods was studied. Three different concentrations of TiO 2 nanoparticles (0%, 1.0%, and 1.5%) were evaluated. The nanoparticles were characterized by means of the transmission electron microscopy and an X-ray diffractometer. The varnish prepared was evaluated for its viscosity, adhesion of the film to the wood, water absorption, and the effects of natural weathering on the color and quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 42 publications
3
35
0
Order By: Relevance
“…Overall, it is interesting to note that the use of smaller TiO 2 nanoparticles (Table 1) led to faster degradation (Figures 2 and 6). As mentioned in the study by Moya et al [76], it is likely that the smaller particles more easily penetrate into the applied coating and interfere with its integral polymer chain structure. Based on the results, it can be concluded that the hydrophobic layers and the oil coating significantly increase the hydrophobicity of natural wood surfaces [14,77].…”
Section: Resultsmentioning
confidence: 97%
“…Overall, it is interesting to note that the use of smaller TiO 2 nanoparticles (Table 1) led to faster degradation (Figures 2 and 6). As mentioned in the study by Moya et al [76], it is likely that the smaller particles more easily penetrate into the applied coating and interfere with its integral polymer chain structure. Based on the results, it can be concluded that the hydrophobic layers and the oil coating significantly increase the hydrophobicity of natural wood surfaces [14,77].…”
Section: Resultsmentioning
confidence: 97%
“…Indeed, the addition of TiO 2 favors the absorption of a great amount of UV rays, thus increasing durability. This behavior was evident in wood samples subjected to either artificial or natural weathering, where degradation and color changes were observed [7,91,99].…”
Section: Nano-tio 2 Hybrids On Woodmentioning
confidence: 92%
“…The addition of TiO 2 nano-particles to coatings for wood such as UV-blocking agents is an extensive practice. From the different polymorphs present in TiO 2 nano-particles, rutile offers greater effectiveness as a stabilizer of photo-oxidation of polymers [91,92]. Rutile is an excellent candidate for UV protection because of its high refractive index (n = 2.7), wide band gap (3.05 eV), ability to scatter solar radiation and absorb UV radiation.…”
Section: Nano-tio 2 Hybrids On Woodmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they stated that water-based varnishes caused colour changing effect on mostly in tannin-rich woods. A recent study by Moya et al (2017) involved that less colour change was observed in 9 kinds of tropical wood samples coated by water-based varnish modified with titanium dioxide nanoparticles after one year of natural weathering process. Detailed examination of high gloss polyurethane and traditional shellac varnishes by Šimůnková et al (2018) showed that polyurethane varnish was much more durable than shellac varnish.…”
Section: Introductionmentioning
confidence: 99%